2015
DOI: 10.1042/bst20140312
|View full text |Cite
|
Sign up to set email alerts
|

Engineering activated protein C to maximize therapeutic efficacy

Abstract: The anticoagulant-activated protein C (APC) acts not solely as a crucial regulator of thrombus formation following vascular injury, but also as a potent signalling enzyme with important functions in the control of both acute and chronic inflammatory disease. These properties have been exploited to therapeutic effect in diverse animal models of inflammatory disease, wherein recombinant APC administration has proven to effectively limit disease progression. Subsequent clinical trials led to the use of recombinan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Eli Lilly and Company announced a worldwide voluntary market withdrawal of Xigris [Drotrecogin alfa (activated)] in 2011 following the PROWESS-SHOCK study which failed to show a survival benefit for patients with severe sepsis and septic shock (41). We have demonstrated that patients who undergo a sepsis evaluation in PICU have homogenous immune responses to endotoxin despite their heterogeneous diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Eli Lilly and Company announced a worldwide voluntary market withdrawal of Xigris [Drotrecogin alfa (activated)] in 2011 following the PROWESS-SHOCK study which failed to show a survival benefit for patients with severe sepsis and septic shock (41). We have demonstrated that patients who undergo a sepsis evaluation in PICU have homogenous immune responses to endotoxin despite their heterogeneous diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…PAR1-mediated cytoprotective can be stimulated in many cell types, including neurons, dendritic cells, astrocytes, epithelial cells, fibroblasts, and others. Cellular signaling responses to APC are complex and PAR1 is not the only relevant substrate mediating its cytoprotection (for reviews see [22,23]). However, knockdown or inhibition of PAR1 blocks cytoprotective effects in many preclinical disease models [22].…”
Section: Par1 Mechanism Of Actionmentioning
confidence: 99%
“…101 Alternatively, signaling-selective engineered APC analogs with diminished anticoagulant properties may offer a safer approach. 102 An alternative potential therapeutic strategy is to use the high affinity of EPCR for PfEMP1 CIDRa1 domains to create recombinant sEPCR analogs that could prevent IE cytoadherence to the vessel wall. To this end, a bioengineered sEPCR analog containing an amino acid substitution (E86A) that has previously been demonstrated to ablate protein C binding was developed.…”
Section: Attenuation Of Anticoagulation Pathwaysmentioning
confidence: 99%